2023
DOI: 10.7717/peerj.14856
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sleep duration and activities of daily living (ADL) disability in the Chinese oldest-old: A cross-sectional study

Abstract: Objective To investigate the relationship between sleep duration and activities of daily living (ADL) disability, and to explore the optimal sleep duration among oldest-old Chinese individuals. Methods In this cross-sectional study, 1,798 participants (73.2% female) were recruited from Dongxing and Shanglin in Guangxi Zhuang Autonomous Region, China in 2019. The restricted cubic spline function was used to assess the dose-response relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…Sleep duration of 6-8 h was connected with the lowest risk of death in a study comprising 116,632 adults, while the optimal amount of sleep duration was roughly 7 h (50). However, one recent study supporting our findings has also highlighted that two more hours of sleep may be advantageous for older adults' daily activities (48). In addition, the impact of baseline and deteriorating frailty states on the increased severity of depression symptoms can be exacerbated by short sleep duration (51), which partly validated our results.…”
Section: Discussionsupporting
confidence: 87%
“…Sleep duration of 6-8 h was connected with the lowest risk of death in a study comprising 116,632 adults, while the optimal amount of sleep duration was roughly 7 h (50). However, one recent study supporting our findings has also highlighted that two more hours of sleep may be advantageous for older adults' daily activities (48). In addition, the impact of baseline and deteriorating frailty states on the increased severity of depression symptoms can be exacerbated by short sleep duration (51), which partly validated our results.…”
Section: Discussionsupporting
confidence: 87%
“…Sleep duration of 6-8 h was connected with the lowest risk of death in a study comprising 116,632 adults, while the optimal amount of sleep duration was roughly 7 h (50). However, one recent study supporting our findings has also highlighted that two more hours of sleep may be advantageous for older adults' daily activities (48). In addition, the impact of baseline and deteriorating frailty states on the increased severity of depression symptoms can be exacerbated by short sleep duration (51), which partly validated our results.…”
Section: Discussionsupporting
confidence: 87%
“…Obtaining approximately 8 to 10 h of sleep per night can even entirely offset the negative effects of decreased ADL on depressive symptoms. It can be speculated that older adults with long sleep duration may elevate their inflammatory markers, leading to an influence on the impairment of their cognition and motion, thus increasing the possibility of ADL disability and ultimately inducing depressive symptoms (48). Luo et al (49) argued that short and long sleep durations amplified the risk of hypertension among Chinese adults, which might result in cardiovascular diseases that impair senior people's capacity for daily activities.…”
Section: Discussionmentioning
confidence: 99%
“…Another study focusing on patients with dementia discovered that a longer sleep duration was associated with ADL disability [ 49 ]. Similarly, a cross-sectional study that recruited 1798 participants older than 90 years found that a long sleep duration (≥12 hours) may be associated with an increased risk of ADL disability for this population [ 19 ]. Peng et al [ 50 ] found that after accounting for potential confounders such as age and gender, both longer and shorter sleep durations were linked to a heightened risk of IADL disability, which was consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%